2019 IEEE International Symposium on Olfaction and Electronic Nose (ISOEN) 2019
DOI: 10.1109/isoen.2019.8823219
|View full text |Cite
|
Sign up to set email alerts
|

Urban Monitoring of Unpleasant Odors with a Handheld Electronic Nose

Abstract: This work describes a real application of artificial olfaction where a handheld electronic nose was used as a validation tool for a chemical spillage in a southern town in Spain. The objective was to check if the palliative and precautionary measurements taken by the authorities were working effectively, removing the elevated values of phenol that were detected in a wide area of the municipality of Coria del Río (Spain). To this end, a gas distribution map of the affected neighborhoods was built with a portabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…A few recent studies undertook novel smellwalks, engaging electronic smellwalks, hybrid human/electro smellwalks, virtual smellwalks, and retrospective smellwalks. One study in Malaga (Spain) tested the feasibility of replacing human smell detection with an e-nose—a wearable electronic nose, for the central reasons that smellmaps created through traditional means are easily outdated, and the effort to conventionally produce them is arduous ( Gongora et al 2018 ). While comparable methodologies were engaged (predetermined locations, different conditions, attribute data of smell type, intensity, and geolocation), each 1 h walk covered significant distances of around 3.5 km ( Gongora et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies undertook novel smellwalks, engaging electronic smellwalks, hybrid human/electro smellwalks, virtual smellwalks, and retrospective smellwalks. One study in Malaga (Spain) tested the feasibility of replacing human smell detection with an e-nose—a wearable electronic nose, for the central reasons that smellmaps created through traditional means are easily outdated, and the effort to conventionally produce them is arduous ( Gongora et al 2018 ). While comparable methodologies were engaged (predetermined locations, different conditions, attribute data of smell type, intensity, and geolocation), each 1 h walk covered significant distances of around 3.5 km ( Gongora et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study in Malaga (Spain) tested the feasibility of replacing human smell detection with an e-nose—a wearable electronic nose, for the central reasons that smellmaps created through traditional means are easily outdated, and the effort to conventionally produce them is arduous ( Gongora et al 2018 ). While comparable methodologies were engaged (predetermined locations, different conditions, attribute data of smell type, intensity, and geolocation), each 1 h walk covered significant distances of around 3.5 km ( Gongora et al 2018 ). While recognized by the researchers that the e-nose smell detection rate was lower than that of a human (including false positive readings), it was suggested that future e-nose research could be improved with an increased data-size and fine-tuning of classifiers ( Gongora et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…RTIFICIAL Olfaction (AO) refers to identifying and discriminating different odors using electronic instruments like an Electronic Nose System (ENS). The ENS has a broad range of applications including the food industry [1]- [3], health sector [4], [5], environment monitoring [6], oil and gas industry [7], and security purposes [8], [9], among others. An ENS is comprised of two units, a sensing unit and a recognition unit.…”
Section: Introductionmentioning
confidence: 99%
“…In this research study, an embedded electronic device is designed to measure the concentration of Odor pollution at selected areas. The design of artificial olfactory electronic nose (Gongora et al, 2019;Erisman, 2001) (EPA, 2021) and then providing the alert information to end users. Finally, the Data processor (Atmega328) coordinates and controls all the peripherals connected to the system, processes the sensor data and sends the sensed information to the Cloud.…”
Section: Introductionmentioning
confidence: 99%